Digital Media-Based Tarikh Learning through a Deep Learning Approach: A Case Study at SMP Muhammadiyah 1 Madiun - Yan Adhi Wikarsa; Hilmy Yunan; Amir Amir; Dina Mardiana (Journal of Teacher Training and Educational Research, 2026)
This study aims to describe and analyze the implementation of digital media-based Tarikh learning with a deep learning approach at SMP Muhammadiyah 1 Madiun. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation involving two Year 8 students, a Tarikh teacher, and the vice-principal for curriculum. The data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing or verification, while data validity was ensured through source triangulation, technique triangulation, and member checking. The findings show that Tarikh learning was innovated through the use of instructional videos, interactive PowerPoint presentations, infographics, visual chronology, and digital storytelling. These media helped students understand Islamic historical events more concretely, increased their engagement, and encouraged discussion and value reflection. The teacher played a central role as a facilitator and innovator by guiding students to analyze moral messages, reflect on prophetic values, and connect Tarikh materials with daily life. School support through curriculum flexibility, learning facilities, and digital learning encouragement also strengthened implementation. The deep learning approach contributed to students’ conceptual, reflective, and applicative understanding, particularly in interpreting values such as honesty, courage, patience, responsibility, and prophetic exemplarity. This study concludes that digital media-based Tarikh learning with a deep learning approach can become an adaptive and meaningful model for Islamic Religious Education in the digital era.